Novel porcine rotavirus of genotype P[27] shares new phylogenetic lineage with G2 porcine rotavirus strain - Khamrin P. (2014)
A novel and unusual strain of porcine rotavirus (PoRV) CMP034 was isolated from a 7-week-old piglet during the epidemiological survey of porcine rotavirus infection in Chiang Mai province, Thailand from June 2000 to July 2001. Molecular characterization of gene VP4 by sequence analysis showed a low level of amino acid sequence identity, ranging from 56.7% to 76.6%, while comparison of VP8* portion showed 41.8% to 69.9% identity, with the 26 P genotypes recognized to date. Phylogenetic analysis of the VP4 sequence revealed that CMP034 was only distantly related to the other 26 P genotypes and was located in a separate branch. Sequence analysis of gene VP7 showed the highest level of amino acid identity (94.7%) with the PoRV G2-like reference strain 34461-4 but a lower level of identity with those of human G2 rotaviruses, ranging from 87.7% to 88.0%. Phylogenetic analysis of gene VP7 revealed two major lineages among G2 rotavirus strains based on the host origin. PoRV strain CMP034 clustered exclusively with G2-like PoRV strain 34461-4 in a novel lineage that is distinct from the major G2 human lineage. Moreover, strain CMP034 displayed a porcine-like VP6 and NSP5/6 with subgroup I specificity, while bearing an NSP4 with some genetic group B human-like characteristics. These findings provide evidence that CMP034 should be considered as a novel VP4 genotype P[27]. © 2006 Elsevier Inc. All rights reserved.